Libyan University EFL Students’ Attitudes toward Pedagogical, Sociocultural, and Psychological Factors Affecting Oral Communication Skills - Hamza Mohamed Muftah; Asma Omar Ammar (Journal of English Language Teaching and Linguistics, 2026)
This study aims to investigate the attitudes of EFL students towards the factors contributing to their poor oral communication skills. The study was conducted at Alajaylat Faculty of Arts and Education, University of Zawia. A quantitative research method was used to identify Libyan EFL postgraduate-level students’ attitudes towards pedagogical, sociocultural, and psychological factors contributing to their poor communication skills. A closed-ended questionnaire was administered to thirty-five EFL students. The findings revealed that students perceive pedagogical factors, such as insufficient interactive classroom activities, a lack of classroom support for spoken English, inadequate opportunities to practice speaking, ineffective teaching methods, and insufficient practice to improve oral skills, as the primary contributors to their weak oral communication skills in English. Moreover, psychological factors, including low self-confidence, foreign language anxiety, and fear of negative evaluation,  were also identified as significant barriers to students’ oral communication development. The study also indicates that sociocultural barriers moderately hinder students’ oral performance, indicating that Sociocultural Factors are not perceived as major barriers compared to pedagogical and psychological factors. This indicates that instructional practices and learners’ affective states have a more significant influence on oral communication development than sociocultural factors in the context of this study. The study suggests the adoption of interactive teaching strategies and the creation of supportive classroom environments to reduce emotional barriers and encourage active oral participation.